Digital Innovation in Pesantren Education: Prediction to Welcome Global Islam Awakening - Ansori Ansori; Dawam Multazamy Rohmatulloh; Didi Sudrajat; Sitti Asnaeni. Am; Sri Utami (Nazhruna: Jurnal Pendidikan Islam, 2022)
This paper aimed to discuss the creativity and innovation of Islamic boarding schools in the digital era. The research method of this study was literature, by looking for related literature contained in books, articles, and websites both national and international publications. The results of this study indicate that pesantren that only survive on the old learning system, without relying on technological sophistication, will be left behind by communities that have implemented a technological system. It is hoped that this discussion is useful for other Islamic educational institutions, it is necessary to carry out various creativity and innovations through technology so that pesantren are more alive not only in the real world but in cyberspace. For similar research, it can be used as comparison material with field studies between traditional and modern Islamic boarding schools throughout Indonesia.